(untitled) (Global Journals of Research in Engineering, 2013)
In this paper a closed loop PI controller is designed to obtain the desired output torque, speed and stator phase current of interior permanent magnet synchronous motor (IPMSM) fed by a three-level diode clamped inverter which is built using twelve IGBTs (Insulated-gate Bipolar Transistor). Model of IPMSM is established using the equations describing dynamic behavior of interior permanent magnet synchronous motor in Matlab-Simulink respectively. Three modulation techniques has been studied, Sinusoidal Pulse Width Modulation (SPWM), Space Vector Pulse Width Modulation (SVPWM) and a novel Carrier Based Space Vector Pulse Width Modulation (CBSVPWM).The complex trigonometric calculations involved in conventional SVPWM techniques creates delay in computations and hence the drive response is weakened. Compared to the conventional SVPWM this method is simpler and avoids complex trigonometric calculations. Using MATLAB/ SIMULINK simulation and analysis of the novel scheme is carried out.